2018
DOI: 10.4049/jimmunol.1701079
|View full text |Cite
|
Sign up to set email alerts
|

CD8 Follicular T Cells Promote B Cell Antibody Class Switch in Autoimmune Disease

Abstract: CD8 T cells can play both a protective and pathogenic role in inflammation and autoimmune development. Recent studies have highlighted the ability of CD8 T cells to function as T follicular helper (Tfh) cells in the germinal center in the context of infection. However, whether this phenomenon occurs in autoimmunity and contributes to autoimmune pathogenesis is largely unexplored. In this study, we show that CD8 T cells acquire a CD4 Tfh profile in the absence of functional regulatory T cells in both the IL-2-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
75
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(84 citation statements)
references
References 56 publications
(90 reference statements)
7
75
1
1
Order By: Relevance
“…To analyze the role of Tfh and Tfr cells in the IL-2 KO, we obtained IL-2 KO mice on the C57BL/6 (B6) background because this strain was genetically compatible with most conditional KO strains that are also on the B6 background. We found that IL-2 KO mice on the B6 background in our facility were healthier than reported for IL-2 KO mice on the BALB/c background (38,39,43). In our colony, most B6 IL-2 KO mice live longer than 5 wk and have a lifespan more similar to what was seen with IL-2 KO mice on the mixed 129-O1a 3 C57BL/6 background (37,38).…”
Section: Tfh Cells But Not Tfr Cells Are Increased In the Absence Of supporting
confidence: 45%
See 3 more Smart Citations
“…To analyze the role of Tfh and Tfr cells in the IL-2 KO, we obtained IL-2 KO mice on the C57BL/6 (B6) background because this strain was genetically compatible with most conditional KO strains that are also on the B6 background. We found that IL-2 KO mice on the B6 background in our facility were healthier than reported for IL-2 KO mice on the BALB/c background (38,39,43). In our colony, most B6 IL-2 KO mice live longer than 5 wk and have a lifespan more similar to what was seen with IL-2 KO mice on the mixed 129-O1a 3 C57BL/6 background (37,38).…”
Section: Tfh Cells But Not Tfr Cells Are Increased In the Absence Of supporting
confidence: 45%
“…Autoantibodies specific for colon cells were detected in these mixed background IL-2 KO mice (37). In BALB/c IL-2 KO mice, high levels of autoantibodies to RBCs lead to severe AIHA and much earlier death than on a mixed background (38,39). In BALB/c IL-2 KO mice, conventional CD4 + Tfh cells are elevated as well as an unusual CD8 + Tfh-like population with B cell helper activity (39).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…areas represent immunologically privileged areas with limited presence of potential CTLs(Connick et al, 2007). Besides their cytolytic activity, fCD8 cells can promote isotype switching of B cells in the settings of autoimmunity(Valentine et al, 2018) while IL-6, a positive regulator of Tfh cells(Eto et al, 2011), can also induce IL21-producing CD8 T cells with follicular helper function(Yang et al, 2016) and therefore further induce humoral responses indirectly through local IL21 production. Despite a trend for higher baseline CD3 hi CD4 lo T cells in old compared to young LNs, a significant positive correlation between Tfh and CD3 hi CD4 lo was found only in young animals, indicating a possible "helper" fCD8 T-cell function in young NHPs.Tissue inflammation and immune activation may play a significant role in follicular immunodynamics(Ferrando-Martinez et al, 2018).…”
mentioning
confidence: 99%